Hungarian Monitoring, 8 August 1990 . [Magyar rádiófigyelő], 1990. augusztus 8 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - On the Romanian opposition movements' prospects - American soldiers arrive in Saudi Arabia - NATO discusses Kuwait - New president of Armenia in talks in Moscow - President Bush's explanation for the Iraqi intervention - Pan-German talks - Trial suspended of genocide suspects Domestic Affairs: - Hungarians missing in Kuwait - László Tőkés's accident - Evolving defense doctrine - Vatra Românească protests against the Hungarian leader of Covasna county Economy: - Drought damage Külpolitika: - A román ellenzéki mozgalmak perspektíváiról - Amerikai katonák érkeznek Szaúd-Arábiába - Kuvait ügyében tárgyal a NATO - Moszkvában tárgyal Örményország új elnöke - Bush elnök magyarázata az iraki beavatkozásra - Össznémet tárgyalások - Felfüggesztik a népirtással vádoltak perét Belpolitika: - Magyar eltűntek Kuvaitban - Tőkés László balesete - Átalakuló védelmi doktrína - Vatra Romaneasca tiltakozás Kovászna megye magyar vezetője ellen Gazdaság: - Aszálykárok